2012
DOI: 10.1007/s11250-012-0203-4
|View full text |Cite
|
Sign up to set email alerts
|

Social and gender determinants of risk of cryptosporidiosis, an emerging zoonosis, in Dagoretti, Nairobi, Kenya

Abstract: The aim of the study was to investigate the social and gender determinants of the risk of exposure to Cryptosporidium from urban dairying in Dagoretti, Nairobi. Focus group discussions were held in six locations to obtain qualitative information on risk of exposure. A repeated cross-sectional descriptive study included participatory assessment and household questionnaires (300 randomly selected urban dairy farming households and 100 non-dairying neighbours). One-hundred dairy households randomly selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…This finding disagrees with the report from Kenya [26]. The authors argued that that exposure to Cryptosporidium was influenced by gender, age and role in the household.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding disagrees with the report from Kenya [26]. The authors argued that that exposure to Cryptosporidium was influenced by gender, age and role in the household.…”
Section: Discussioncontrasting
confidence: 86%
“…In a study conducted in Kenya, it was reported that there were no diff erences between the genders regarding the knowledge for a zoonotic disease analyzed, but that the women were in the risk group for the zoonotic diseases 22 . Th e result of the study is consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pereira et al (2002) have also shown that the risk of infection among male patients was 2.2 times higher as compared to that in females among children hospitalized for diarrhea in Brazil. Kimani et al (2012) have observed the proportion of males to be 3.35 times higher as compared to that of females in a study conducted at Kenya. Higher risk to males in developing countries could be attributed to higher prevalence of manual jobs, unhygienic conditions of work and eating environment and gender wise differentiation of occupations, which involve higher proportion of males as compared to females thus enhancing the risk of males as compared to females.…”
Section: Discussionmentioning
confidence: 90%